The use of statistics in engineering and food industry / Norazah Umar and Zuraira Libasin - Umar, Norazah; Libasin, Zuraira (Unit Penerbitan JSKM, 2020)
Statistics is an important tool for robustness analysis, measurement system error analysis, test data analysis and it is extremely important in our daily life. In this article we will discuss some examples of the importance of statistics in engineering and food industry as these are the two main programs available in UiTM Permatang Pauh. An engineer is someone who solves problems of interest in society by either refining an existing product or design a new product that meets customers' needs. Knowledge of statistics is important to engineers because some statistical techniques can be a powerful aid in designing new products and systems, improving existing designs, developing new design and improving production processes. Some of the most important statistics applications in the field of engineering are Probability Application, Experimental Design, Hypothesis Testing, Quality Control and Regression Analysis.